Preliminary Assessment of Air During COVID-19 Lockdown: An Unintended Benefit to Environment: DOI: 10.32526/ennrj.18.4.2020.35 - Pervaiz, Shazia; Javid, Kanwal; Zafar Khan, Filza; Zahid, Younis; Akram, Muhammad Ameer Nawaz (Environment and Natural Resources Journal, 2020)
The death rate of people is increasing globally during the current outbreak of coronavirus. To combat with COVID-19 havoc, the world has adopted lockdown policy including Pakistan. Ironically, the invisible virus is suffocating humans at a fast rate but on the other side, there is another visible monster in the world gobbling up human’s health i.e. air pollution. Therefore, the main rationale of the present research is to visualize the air quality by mapping via online tools and techniques using geospatial system during the ‘Lockdown’ period in Lahore, Pakistan. According to the present findings, the fluctuation in the concentration of air pollution is visualized all over the city under Punjab Environmental Quality standards (PEQs). The ﬁndings of the present study also revealed that due to suspended human activities during COVID-19 disaster, the air quality level is satisfactory for public health in Lahore. So, in the light of results once this COVID-19 crisis will be over, government should speed up measures to lessen air pollution to achieve targets of sustainable development goals (SDGs). Moreover, the present results of air assessment during COVID-19 would serve as a useful reminder for the government of Punjab to cut down air emissions level after pandemic.